Menjalankan Kekuatan Eksekutorial Sertifikat Fidusia Terhadap Benda Jaminan oleh Ketua Pengadilan - Hefi Yudiyanto; Faisol Abrori (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The executorial power contained in the provisions of article 15 paragraph (2) of the Fiduciary Guarantee Law, makes the position of a fiduciary guarantee certificate equivalent to a court decision which has permanent legal force (inkracht van gewijsde). This executorial power is based on the mandate "For Justice Based on Belief in One Almighty God" as stated in the Fiduciary Guarantee Certificate. The consequences of this irrah-irah have legal consequences for the parties. Therefore, it is interesting to study these two legal products. The analysis was carried out on primary data in the form of main legal materials, namely the provisions of Article 15 paragraph (1), (2), Fiduciary Guarantee Law no. 42 of 1999 and provisions in the Civil Procedure Law Article 224 HIR, Article 258 Rbg. Data collection techniques were carried out using document studies and analyzed perspectively and descriptively. The research results show that a fiduciary certificate does not have executorial power as long as it does not receive an order from the Chief Justice through a Court decision.